Differential Intensity Modulation Refractometer Based on SNS Structure Cascaded Two FBGs - Cheng Zhang; Shan Xu; Junfa Zhao; Hongqiang Li; Hua Bai; Changyun Miao (IEEE Photonics Journal, 2017)
A differential intensity modulation refractometer based on single-mode-no-core-single-mode (SNS) structure cascaded with two fiber Bragg gratings (FBGs) is proposed. The SNS structure acts as a band pass fiber (BPF), and the Bragg wavelengths of the two FBGs located at each edge of the BPF. Because the interference spectrum of the SNS is sensitive to refractive index (RI) but FBG is not, the reflective powers of the FBGs are modulated by the surrounding refractive index (SRI) and have contrary changing trends. The reflective intensity difference of the FBGs is used to describe the change of the SRI, which not only increases the RI sensitivity but diminishes the influence of the input light fluctuation as well. In addition, as the SNS and the FBGs have approximate temperature sensitivities, this sensor can accomplish temperature self-compensation. The experiments show that the RI sensitivity of this sensor is about –199.6 dB/RIU in the range of 1.3326–1.3702 and –355.5 dB/RIU in the range of 1.3702–1.4066, which is greater than the traditional SNS-FBG structure. However, its temperature sensitivity is only 0.0148 dB/°C. When the input light varies 7 mW, the shift of the intensity difference is only 0.28 dB, which is much smaller than the intensity shift of the single FBG.